Enhancement of apple coloration using jasmonate treatment without sacrificing storage potential. (2nd January 2018) - Liu, Weiting; Li, Tong; Yuan, Hui; Tan, Dongmei; Wang, Aide
ABSTRACT: Apple coloration is very important for most cultivars. The application of jasmonate can effectively enhance the coloration of apple fruit, but it might ruin the fruit's storage potential. Here, we report that applying methyl jasmonate on apple fruit 3 weeks before commercial harvest not only enhanced the fruit coloration but also did not affect its storage potential. Our findings provide important information for enhancing apple coloration using jasmonate.